2011
DOI: 10.1371/journal.pone.0016530
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Pancreatic Cancer Stem Cell Characteristics in Human and KrasG12D Transgenic Mice by Inhibiting Pluripotency Maintaining Factors and Epithelial-Mesenchymal Transition

Abstract: BackgroundCancer stem cells (CSCs) can proliferate and self-renew extensively due to their ability to express anti-apoptotic and drug resistant proteins, thus sustaining tumor growth. Therefore, the strategy to eradicate CSCs might have significant clinical implications. The objectives of this study were to examine the molecular mechanisms by which resveratrol inhibits stem cell characteristics of pancreatic CSCs derived from human primary tumors and KrasG12D transgenic mice.Methodology/Principal FindingsHuman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
242
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(247 citation statements)
references
References 80 publications
3
242
0
1
Order By: Relevance
“…This indicates that the EMT process is regulated by the Hh signaling pathway. Another previous study demonstrated that resveratrol could inhibit EMT in order to slow migration and invasion in pancreatic cancer cells (51).…”
Section: Discussionmentioning
confidence: 95%
“…This indicates that the EMT process is regulated by the Hh signaling pathway. Another previous study demonstrated that resveratrol could inhibit EMT in order to slow migration and invasion in pancreatic cancer cells (51).…”
Section: Discussionmentioning
confidence: 95%
“…6 It has also shown chemopreventative properties in certain forms of cancer and cardiovascular disorders and to increase longevity. [7][8][9] Moreover, resveratrol appears to protect against diabetes 10 by inducing silent information regulator 2-related enzymes 1 (sirtuin1, SIRT1). 11 In this study, we investigated the hypothesis that resveratrol improved erectile function in diabetes-induced ED by suppressing apoptosis and preventing oxidative stress in the corpus cavernosal and by upregulating SIRT1 in a streptozotocin (STZ)-induced diabetic rat model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that transformed epithelial cells may activate embryonic programs for epithelial plasticity and switch from sessile and epithelial phenotypes to motile and mesenchymal phenotypes (30). Therefore, the induction of EMT may lead to the invasion of surrounding stroma, intravasation, dissemination and colonization of distant sites (31). Under the CSC hypothesis, sustained metastatic growth requires the dissemination of a CSC from the primary tumor followed by its reestablishment at a secondary site (32).…”
mentioning
confidence: 99%